Reframing Social Studies Education : A Critical Pedagogical Approach to Developing Students’ Ecological Awareness - Jumriani Jumriani; Deasy Arisanty; Ersis Warmansyah Abbas; Mutiani Mutiani (Jurnal Paedagogy, 2026)
This study analyzes the role of a critical pedagogical approach in Social Studies education in strengthening students’ ecological awareness. The research employs a qualitative approach using a literature review method. Data were drawn from 27 selected scholarly publications sourced from Scopus-indexed journals and nationally accredited journals. These publications were analyzed through a conceptual literature review and qualitative content analysis to identify key themes related to critical pedagogy, Social Studies education, and ecological awareness. The findings indicate that critical pedagogy enables the meaningful integration of environmental issues into Social Studies learning by fostering contextual, dialogical, and reflective learning processes. Through the problematization of socio-ecological realities, students are encouraged to develop an understanding of the interrelationships between human activities, development policies, and their environmental impacts. This approach not only enhances cognitive understanding but also cultivates students’ critical awareness, environmental concern, and ecological responsibility. The study concludes that Social Studies learning grounded in critical pedagogy can function as a vehicle for social transformation by promoting ecological awareness. It further emphasizes the importance of shifting the Social Studies learning paradigm from memorization-oriented instruction toward meaningful, critical learning oriented to environmental sustainability.